The factors of students' anxiety in speaking english:case study of eight grade SMP Negeri 3 Pelepat Ilir - Titik Nurchasanah Titik Nurchasanah; Diana Oktavia; Nur Habibah (Universitas Muhammadiyah Muara Bungo, 2025)
Anxiety in speaking English is a common problem experienced by students, especially at the junior high school level, and can hinder their language learning process. Therefore, it is important to identify the underlying factors that underlie the appearance of students' anxiety in speaking English. This study aims to explore and analyze the factors that cause anxiety in English speaking in grade VIII students at SMP Negeri 3 Pelepat Ilir. This study uses a qualitative research design with data collection techniques in the form of interviews and observations. Using the Interview Guideline and Observation Sheet instruments. The study participants consisted of five students who were selected purposively based on criteria such as low academic achievement and lack of confidence. The analysis technique is based on Miles and Huberman 1994, with thematic analysis based on Braun and Clarke 2006. The results of the study show that there are four main factors that cause students' anxiety, namely fear of making mistakes, lack of confidence, nervousness, and low motivation. These findings confirm the importance of creating a supportive learning environment and a positive teaching approach to help students overcome anxiety in speaking English. It was found that there was a dominant factor that had the most influence on students. One of them is the factor of lack of internal trust where there is an external cause. All four students have explained the reasons why they feel less confident. Namely lack of understanding of the material, fear of being the center of attention in class, and feeling insecure. This lack of confidence is also shown on the pitch. This factor becomes dominant because almost all students feel anxious, causing students to become less confident when trying to speak English in front of the class.